Численность и распределение мигрирующих кроншнепов на юго-восточном побережье Каркинитского залива в 2001-2002 гг. - Попенко, В.М.; Черничко, Р.Н.; Костин, С.Ю.; Тарина, Н.А.; Багрикова, Н.А. (Бранта: Cборник научных трудов Азово-Черноморской орнитологической станции, 2003)
Работы проводились по проекту Украинского общества охраны птиц при спонсорской поддержке Bird Life International и UNEP/CMS в 2001-2002 гг. Район наблюдений охватывал побережье Каркиницкого залива от Кумовских плавней на востоке до Бакальской косы на западе (рис 1), включая морские отмели. Видовой состав и численность птиц определялась на 6 стандартных маршрутах. Коды биотопов приводятся в соотвествии с Классификацией местообитаний Палеарктики по типологической схеме CORINE. Роботи проводились за проектом Українського товариства охорони птахів при спонсорській підтримці Bird Life International та UNEP/CMS в 2001-2002 рр. Район спостережень охоплював узбережжя Каркінітської затоки від Кумовських плавнів на сході до Бакальскої коси на заході (рис 1), включаючи морські мілини. Видовий склад і чисельність птахів визначались на 6 стандартних маршрутах. Коди біотопів наводяться у відповідності з Класифікацією місцеперебувань Палеарктики за типологічною схемою CORINE. The work was carried out according to the project of Ukrainian Society for Bird Conservation and owing to sponsor support of Bird Life International and UNEP/CMS in 2001-2002. The area of observations covered the coast of Karkinitsky bay from Kumovskaya plavni in the east to Bakalskaya spit in the west (Fig.1) including sea shoals. Species composition and number of birds were counted along 6 standard routes. Observations of Curlews were taken from hides at the distance of 60-500 m. Binoculars with 8-20 times magnification and telescopes with 15-40 times magnification were used. Codes of biotopes correspond to Classification of Palearctic habitats following the CORINE typological scheme.